The Ontological Dissonance of Corporate Degrowth : Deconstructing Multinational Strategic Contraction and Supply Chain Dematerialization Amidst Mandatory Global Consumption Thresholds - Aldi Adi Pratama (Indonesian of Interdisciplinary Journal, 2025)
Modern management discourse currently faces an existential crisis due to an absolute dependence on economic growth that exceeds the planet's ecological boundaries. This research aims to dissect the narrative of strategic contraction in multinational corporations (MNCs) and explore the application of dematerialization concepts amidst the fundamental contradictions of traditional management logic. The methodology employed is an aporetic and iterable deconstruction model, encompassing a Double Commentary phase to map the internal logic of MNC strategic documents and Disruptive Reading to expose the internal contradictions within corporate narratives. The results indicate that corporations are trapped in ontological dissonance; operational reduction measures are often parasitic to capital accumulation, as they are only implemented in non-competitive units while growth ambitions are maintained in other sectors. Furthermore, dematerialization through servitization schemes faces significant barriers in the form of linear cultural inertia and short-term profitability dilemmas. It is concluded that authentic sustainability demands a radical revision of organizational identity, where planned operational reduction and the adoption of absolute ecological allowance standards become imperative. Strategic recommendations include the use of absolute performance metrics reflecting Earth system boundaries and the redefinition of organizational purpose through ontological diagnostics to achieve systemic resilience in an era of global consumption thresholds.